The World of our little friends: The Ants - "Yahya, Harun" (Goodword Books: New Delhi, 2001)
This children's book introduces readers to the fascinating world of ants, highlighting their intricate social structures, industrious nature, and the lessons they offer about cooperation and community. Through engaging narratives and vivid illustrations, the book aims to inspire curiosity and appreciation for these small yet remarkable creatures. It also emphasizes the wonders of creation, encouraging children to reflect on the natural world's complexities.
Keywords: Ants$1 (BJuvenile Literatures